2023
DOI: 10.1111/ene.15746
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers predictive of atrial fibrillation in patients with cryptogenic stroke. Insights from the Nordic Atrial Fibrillation and Stroke (NOR‐FIB) study

Abstract: Background and purpose There are currently no biomarkers to select cryptogenic stroke (CS) patients for monitoring with insertable cardiac monitors (ICMs), the most effective tool for diagnosing atrial fibrillation (AF) in CS. The purpose of this study was to assess clinically available biomarkers as predictors of AF. Methods Eligible CS and cryptogenic transient ischaemic attack patients underwent 12‐month monitoring with ICMs, clinical follow‐up and biomarker sampling. Levels of cardiac and thromboembolic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…21) NT-proBNP was found to be a predictor of stroke in patients with AF. 13) In a subanalysis of ENGAGE AF-TIMI 48, the prognostic value of NT-proBNP for stroke in patients with NVAF was further verified. 22) The mechanism of NT-proBNP as a predictor of stroke risk in patients with NVAF may be that the increase in NT-proBNP may reflect atrial structural and functional impairments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…21) NT-proBNP was found to be a predictor of stroke in patients with AF. 13) In a subanalysis of ENGAGE AF-TIMI 48, the prognostic value of NT-proBNP for stroke in patients with NVAF was further verified. 22) The mechanism of NT-proBNP as a predictor of stroke risk in patients with NVAF may be that the increase in NT-proBNP may reflect atrial structural and functional impairments.…”
Section: Discussionmentioning
confidence: 93%
“…There are few research on clinically independent risk factors for low-risk NVAF (other than the CHA2DS2-VASc score). [12][13][14] Additionally, little study has been done on the prognosis of low-risk NVAF patients who experience stroke, including in-hospital mortality. Investigating the traits of patients with ischemic stroke and poor prognosis among individuals at low risk according to the CHA2DS2-VASc score is therefore important.…”
mentioning
confidence: 99%
“…Advanced machine learning algorithms may also aid in the prognostication of patients with suspected AF [ 40 ]. In addition to NT-proBNP, other biomarkers have been traditionally used; however, their efficacy in detecting AF has been variable and comparatively suboptimal for clinical use [ 41 ]. A detailed overview of these biomarkers is provided in Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, standard cardiovascular laboratory parameters such as triglycerides and total cholesterol have also been shown to enhance the ability of NT-proBNP to distinguish between stroke of cardioembolic or large-artery atherosclerotic origin [ 54 ]. A recent prospective study also identified several biomarkers associated with AF in cryptogenic stroke patients [ 41 ]. Notably, NT-proBNP emerged as the robust predictor of AF at baseline and after 12-month follow-up [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation